2018
DOI: 10.1001/jamanetworkopen.2018.5446
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Coronary Intervention in Patients Without Acute Myocardial Infarction in China

Abstract: Key Points Question What is the self-perceived angina-specific health status before and after percutaneous coronary intervention (PCI) among patients without acute myocardial infarction in China? Findings In this cohort study of 1611 Chinese patients without acute myocardial infarction undergoing elective PCI, 27.5% had stable coronary artery disease and 72.5% had unstable angina. Of patients undergoing PCI for stable coronary artery disease, 25.7% had no r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…It is in this context that the study by Lu et al sheds new insights. Lu et al considered the extent to which 1611 patients enrolled in the large China Patient-Centered Evaluative Assessment of Cardiac Events (PEACE) Prospective Study—and who received PCI in the absence of MI—benefited from treatment . The analysis expands our understanding of how PCI is used in the world’s most populous country in several fundamental ways.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…It is in this context that the study by Lu et al sheds new insights. Lu et al considered the extent to which 1611 patients enrolled in the large China Patient-Centered Evaluative Assessment of Cardiac Events (PEACE) Prospective Study—and who received PCI in the absence of MI—benefited from treatment . The analysis expands our understanding of how PCI is used in the world’s most populous country in several fundamental ways.…”
mentioning
confidence: 92%
“…Irrespective of these reasons, the study findings by Lu et al 4 raise concern that many patients could be exposed to the risks of an invasive procedure with a low likelihood of benefit. Fortunately, in patients who did self-report angina symptoms, most (>90%) reported symptom relief at 1 year, and roughly half of patients reported improved quality of life 1 year after PCI.…”
mentioning
confidence: 99%
“…However, there have not been many studies, including in lower-resource settings, where cardiac and/or PCI outpatients are followed to determine their rate of adverse cardiovascular events (ACE), risk factor control and quality of life (QoL), including angina symptoms [5,6,10]. We know that risk of recurrent events is even higher in those with CVD who also suffer from psychosocial distress such as depression and anxiety as well as sleep issues [11,12], and this type of distress can be higher in China [13].…”
Section: Introductionmentioning
confidence: 99%
“…The high rate [ 3 ] of PCIs performed has led to concerns about the appropriateness, risks and benefits of these procedures in patients who undergo them [ 5 ]. Indeed, in one study which tracked 1600 Chinese patients who underwent PCI for stable coronary artery disease, they found that 26% of the patients had no pre-procedural angina symptoms [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation